2019
DOI: 10.15663/wje.v24i1.644
|View full text |Cite
|
Sign up to set email alerts
|

Use of theories and models in geometry education research: A critical review

Abstract: The aim of this article is to provide a critical review of the theories and the model used in the field of geometry education research. The article critically discusses van Hiele’s theory, Fischbein’s theory of figural concepts, Duval’ s theory of figural apprehension, the Spatial Operational Capacity (SOC) model by Wessels and van Niekerk, and the Sfard’s commognition theory. The van Hiele’s theory proposed a sequential order of development through which the learners construct thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Therefore, one of the problems with this finding is because there are concepts that are not involved in the abstraction process. On the other hand, this case also sheds light on the terms that quotes by Sharma (2019) as a prototypical figural concept in students' understanding of the prism, that is students do not recognize the cube as a special representation of prism even though they are familiar with the conceptual nature of the prism.…”
Section: Abstracting For Relationship Between Propertiesmentioning
confidence: 88%
See 2 more Smart Citations
“…Therefore, one of the problems with this finding is because there are concepts that are not involved in the abstraction process. On the other hand, this case also sheds light on the terms that quotes by Sharma (2019) as a prototypical figural concept in students' understanding of the prism, that is students do not recognize the cube as a special representation of prism even though they are familiar with the conceptual nature of the prism.…”
Section: Abstracting For Relationship Between Propertiesmentioning
confidence: 88%
“…Rahayu and Alghadari (2019) calls it a subjective concept identity and not the same as universally agreed-upon ideas. In fact, the conceptual aspect guarantees the accuracy and logical consistency of the operation (Sharma, 2019). In contrast to many students who construct a rectangular prism model.…”
Section: Abstraction Thinking For Actualizing Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, demonstrating knowledge using an actual didactic instrument enables visually grasping the spatial context provided by a threedimensional model. In turn, it favors a better understanding between what is observed in the model and what was algebraically estimated (Sharma, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…The van Hiele level of geometric thinking indicated that the students at secondary level are in 'formal deduction' level -3. They can apply logical arguments to solve problems and apply the properties of geometric figures to construct (Sharma, 2019). They can construct more complex geometric figures with given conditions and use deductive reasoning to explain why their constructions are valid.…”
Section: Introductionmentioning
confidence: 99%